Implementation of stroke protocol: Insights from a tertiary care facility in urban India - Neha Sharma; Shweta Tyagi; Nitin Jain; Rajnish Kumar; Govind Prakas; Nitisha Goyal (MGM Journal of Medical Sciences)
Background: Stroke is the second leading cause of death globally and ranks third for combined death and disability. Over the past two decades, there has been a significant rise in stroke incidence, mortality, and morbidity, with low- and middle-income countries being disproportionately affected. The effectiveness of thrombolytic therapy for acute ischemic stroke has led centers specializing in acute stroke care to develop protocols for rapid identification and triage of stroke patients. It is recommended that various stakeholders be educated on recognizing and managing stroke early and implement stroke protocols to improve coordination between different departments. Materials and Methods: The study was conducted in the emergency department of a tertiary care center in urban India from September 2021 to September 2022. We aimed to determine the average door-to-imaging (DTI) and door-to-needle (DTN) times for patients presenting with acute ischemic stroke. Additionally, we examined the factors contributing to delays in DTN time management of acute ischemic stroke at our center. Results: During the one-year study period, 131 patients with acute stroke presented to our center. One patient was under 18 years old, 10 patients arrived more than 4.5 h after symptom onset, and 2 patients had contraindications for thrombolysis. Consequently, 118 patients were included in the study. The average DTI time was 23 min, and the average DTN time was 58 min. Of these, 106 patients (89.8%) had a DTN time of less than 60 min. The most common cause of treatment initiation delay was obtaining consent (n = 7; 58.3%), followed by an unreliable time of symptom onset (n = 3; 25%) and delays due to resuscitation (n = 2; 16.6%). Conclusion: Acute stroke is a time-sensitive emergency where early thrombolysis can significantly reduce both morbidity and mortality. However, due to a lack of awareness and accessible resources, many patients often arrive outside the treatment window. Despite these limitations, a substantial number of patients do reach the hospital in time. Implementing a stroke protocol and utilizing innovative methods to reduce time can ensure these patients benefit from the global “standard of care” treatment for stroke.